Groundwater Hydrochemistry in Central Kerala: Implications for Aquifer Infrastructure and Environmental Water Management - Samreena Mohammed; Arunkumar K.S. (CV. Truly Science Publishing, 2025)
Background: Hydrochemistry of groundwater is variable with location in Central Kerala dominated by sedimentary groundwater aquifers. Groundwater chemistry is also greatly influenced by activities to which humans engage in, like rock weathering during contact. Hydrochemical analysis is a basic tool to identify water types and their chemical compositions, as well as to determine whether a water is of a certain quality, which is an important requirement in any water use licensing project. Aim: This study aims to assess the hydrochemical data of groundwater samples. Methods: Sample collected from 70 open wells in and around the Thrissur Ponnani Kol in Central Kerala, through integrated statistical, Piper trilinear diagram, and spatial interpolation methods. Results: The results of this study show that Ca + and Cl− are the dominant cations and anions in the groundwater with mean concentrations of 267.39 mg/l and 574.81 mg/l, respectively. The pre-monsoon Piper: Hydrochemical facies of groundwater in the study area are depicted by plotting the relative concentration of the major cations (Ca²⁺, Mg²⁺, Na⁺, K⁺) and anions (SO₄²⁻, Cl⁻, HCO₃⁻) in the Fig. Most groundwater samples in the study sequences belong to the calcium-bicarbonate (Ca-HCO₃) type, and most of the data points are located close to the Ca²⁺-Mg²⁺ and CO₃²⁻-HCO₃⁻ vertices, suggesting the predominance of carbonate weathering processes. Indicates little exchange of Na⁺, K⁺, Cl⁻, and SO₄²⁻, weak anthropogenic impact, like agricultural runoff or industrial discharge. Conclusion: Thus, the clustering of grouped samples denotes localized groundwater chemistry variations likely due to differences in geology and/or recharge conditions.